Macroeconomic Forecasts in Models with Bayesian Averaging of Classical Estimates - Piotr Białowolski; Tomasz Kuszewski; Bartosz Witkowski (Contemporary Economics, 2012)
The aim of this paper is to construct a forecasting model oriented on predicting basic macroeconomic variables, namely: the GDP growth rate, the unemployment rate, and the consumer price inflation. In order to select the set of the best regressors, Bayesian Averaging of Classical Estimators (BACE) is employed. The models are atheoretical (i.e. they do not reflect causal relationships postulated by the macroeconomic theory) and the role of regressors is played by business and consumer tendency survey-based indicators. Additionally, survey-based indicators are included with a lag that enables to forecast the variables of interest (GDP, unemployment, and inflation) for the four forthcoming quarters without the need to make any additional assumptions concerning the values of predictor variables in the forecast period. Bayesian Averaging of Classical Estimators is a method allowing for full and controlled overview of all econometric models which can be obtained out of a particular set of regressors. In this paper authors describe the method of generating a family of econometric models and the procedure for selection of a final forecasting model. Verification of the procedure is performed by means of out-of-sample forecasts of main economic variables for the quarters of 2011. The accuracy of the forecasts implies that there is still a need to search for new solutions in the atheoretical modelling.
Keywords: C10; C83; E32; E37; 330; Bayesian averaging of classical estimates; business survey data; seasonality; automatic forecasting